Major Ion Concentrations in WDC05Q and WDC06A Ice Cores (WAIS Divide) - Cole-Dai, Jihong (IEDA: US Antarctic Program Data Center, 2014)
Abstract: This data set contains major ion concentrations from the chemical analysis of two WAIS Divide ice cores (WDC05Q, 0-114 m; WDC06A, 0-129 m). The analytical technique is Mettler-based Continuous Flow Analysis with online Ion Chromatography detection (CFA-IC). Depth resolution is approximately 2 cm per sample or per measurement.